2014
DOI: 10.1021/cb500765e
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Structural Changes of Prion Protein during Conversion from α-Helical Monomer to β-Oligomers by Means of ESR and Nanochannel Encapsulation

Abstract: Under nondenaturing neutral pH conditions, full-length mouse recombinant prion protein lacking the only disulfide bridge can spontaneously convert from an α-helical-dominant conformer (α-state) to a β-sheet-rich conformer (β-state), which then associates into β-oligomers, and the kinetics of this spontaneous conversion depends on the properties of the buffer used. The molecular details of this structural conversion have not been reported due to the difficulty of exploring big protein aggregates. We introduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 34 publications
0
15
1
Order By: Relevance
“…This explains the apparent discrepancy between the HX-MS and FRET monitored conformational changes in α3 during the course of oligomer formation. Importantly, these results are in contrast to EPR studies carried out at neutral pH, on disulfide-free mutant variants of the PrP in nanodiscs, which had suggested that α1 and α3 retain their helicity, and that only α2 undergoes conversion to the β-conformation (Yang et al, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…This explains the apparent discrepancy between the HX-MS and FRET monitored conformational changes in α3 during the course of oligomer formation. Importantly, these results are in contrast to EPR studies carried out at neutral pH, on disulfide-free mutant variants of the PrP in nanodiscs, which had suggested that α1 and α3 retain their helicity, and that only α2 undergoes conversion to the β-conformation (Yang et al, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…Another physical method, spin-label electron spin resonance (ESR) spectroscopy, has also been used as a spectroscopic ruler to locate the cross-β structure in inhomogeneous fibrils or oligomers and to explore the structural conversion and aggregation of proteins or peptides such as amyloid β-peptides, tau, transthyretin, and prion protein. [19][20][21][22][23][24][25][26][27][28] In this method, nitroxide spin-labels are introduced into the prion molecule, and one can measure the spin-spin interaction between two unpaired electrons at a distance within 20 Å using continuouswave ESR (CW-ESR) and 15 to 60 Å using double electron-electron resonance (DEER) ESR. 13,29,30 To investigate biomolecules with spin-labeled ESR, a nitroxide-based probe is attached through site-directed spin-labeling (SDSL) mutagenesis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a disulfide bond stabilizes prion protein. Without the disulfide bond, the second α-helix of prion protein is unfolded at room temperature, neutral pH, and in the absence of denaturant, and this partially unfolded prion protein gradually assembles into β-oligomers or fibrils 4 , 5 . The misfolding kinetics is driven by hydrophobic interaction and can be tuned by salt concentration in the protein solution.…”
Section: Introductionmentioning
confidence: 99%